Challenges and issues in team gamer loyalty for massively multiplayer online game - Abdullah, Lili Nurliyana; Gong, Xiaoxue; Mohd Norowi, Noris; Jantan, Azrul Hazri (Springer Nature, 2024)
As the number of players in Massively Multiplayer Online Games (MMOG) increases, the complexity of game missions requires players to work in teams to accomplish game objectives. If players lack expertise in collaboration, they may have difficulty integrating into the game team, which may further erode their loyalty to the MMOG. However, little is known about how game cooperation affects players’ loyalty to MMOG, suggesting that there is a dearth of research in this area. As a result of this mismatch, game developers are unable to allocate resources in ways that increase gamer loyalty. We propose a new framework for the study of team gamer loyalty. The results show that game team norm identification, team participation experience, and cooperative knowledge all contribute to team gamer loyalty. The study suggests that cooperative knowledge among players not only directly increases gamer loyalty, but also amplifies the effects of team participation experience and game team norms on loyalty, which is valuable information for game developers.